Impact of soil degradation on crop production in Brazil - Corsini, P. C. (Elsevier, 1991)
A conceptual model is proposed to facilitate understanding of the effects of soil and crop management practices on soil properties, yields, economics and political interference in production from heavy clay oxisols of the Brazilian developed regions. This model was developed for illustrative purposes, and was established by qualitative and quantitative analyses of data and observations on the rates of change of soil structure, the susceptibility of soils to this changes, and its effects on different cropping systems. Rates of production, technological aspects of production, production efficiency and profitability are compared. In general, the model is presented as a hypothetical function for characterizing and facilitating understanding of the impact of soil degradation on several aspects of crop production from oxisols in Brazil. © 1991.